The development of spallation target and fuel handling system for China initiative accelerator driven system. (15th December 2020) - Li, Jin-Yang; Gu, Long; Xu, Hu-Shan; Zhang, You-Peng; Yao, Cun-Feng; Sheng, Xin; Yang, Sheng; Fan, Da-Jun; Wang, Da-Wei
Highlights: Spallation target and fuel handling system has been developed based on VR platform. The movement of spallation target has been detailed in the fuel handling process. The collision detection and the real-time roaming experience have been discussed. The fuel handling system can cover all the assemblies in subcritical reactor. Abstract: The China initiative Accelerator Driven subcritical System (CiADS) has already embarked on a plan to be built in south China's Guangdong province for the research purpose of lead–bismuth cooled fast reactor and minor-actinide transmutation technology. In comparison with the other critical reactors, it is difficult to arrange the fuel handling equipment and to make the whole core refueling plan, since there is a proton beam tube in the central of the core and the operating environment is completely opaque. In this context, an innovation design of the spallation target and fuel handling system is proposed in Institute of Modern Physics, Chinese Academy of Sciences (IMPCAS) based on an immersive Virtual Reality (VR) platform, which can fulfill the loading and refueling procedure without mutual collisions, and provide the real-time roaming experience as in the real world. Detailed information of the handling system have been introduced including the optimized logical structure in consideration of the movement of spallation target for the fuel handling process, the principle of collision detection based on the fast ray-casting technology, the real-time roaming experience with feedback control in refueling procedure, and the reliability assessment and sequential optimization for the above process. The spallation target and fuel handling system can cover all the assemblies in subcritical reactor and provide a powerful tool for the frequently updated engineering design of the CiADS project.